2009
DOI: 10.1111/j.1365-2435.2009.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of heat‐induced thermal stress resistance and hsp70 expression in the springtail, Orchesella cincta

Abstract: Summary 1.The relationship between thermal resistance and expression of inducible heat shock proteins, especially Hsp70, depends on the species and temperature treatments. The induction of Hsp70 has been shown to be essential for heat stress survival in a number of species, yet the maximum protein expression levels do not coincide with peak survival after heat hardening in Drosophila . 2.Here we study the functional relationship between heat-induced expression of the heat shock protein Hsp70, and thermal resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 46 publications
8
104
1
1
Order By: Relevance
“…Several studies have found a positive correlation between heat tolerance and HSP70 expression (Bahrndorff et al, 2009), whereas others have shown opposite or no correlations (Dahlgaard et al, 1998;Bahrndorff et al, 2009Bahrndorff et al, , 2010. Using the same treatments as herein a previous study on B. anynana, we showed that exposure for 2 h to 39 1C strongly increased subsequent heat-stress survival (Franke and Fischer, 2013), suggesting that a positive relationship between HSP70 expression and heat tolerance exists also in our study organism.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have found a positive correlation between heat tolerance and HSP70 expression (Bahrndorff et al, 2009), whereas others have shown opposite or no correlations (Dahlgaard et al, 1998;Bahrndorff et al, 2009Bahrndorff et al, , 2010. Using the same treatments as herein a previous study on B. anynana, we showed that exposure for 2 h to 39 1C strongly increased subsequent heat-stress survival (Franke and Fischer, 2013), suggesting that a positive relationship between HSP70 expression and heat tolerance exists also in our study organism.…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, the degenerate primers amplify various isoforms, and thus, primers specific to the different isoforms need to be designed on the basis of the sequences obtained with degenerate primers (e.g. as in Bahrndorff et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Köhler et al 1998;Schill et al 2004;Reuner et al 2008;Bahrndorff et al 2009). Degenerate primers targeting the highly conserved nucleotide-binding domain of the hsp70 gene proved useful in amplifying stress protein genes in various animal taxa and subsequent determination of hsp70 nucleotide sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations